Respostas
respondido por:
0
F(1) = 4
y = ax + b
4 = a.1 + b
a + b = 4
F(3) = -2
y = ax + b
-2 = a.3 + b
3a + b = -2
2a = -6
a = -6/2
a = -3
a + b = 4
-3 + b = 4
b = 4 + 3
b = 7
a = -3 e b = 7
y = ax + b
y = -3x + 7
F(x) = -3x + 7
F (7) = -3.(7) + 7
F (7) = -21 + 7
F (7) = -14
y = ax + b
4 = a.1 + b
a + b = 4
F(3) = -2
y = ax + b
-2 = a.3 + b
3a + b = -2
2a = -6
a = -6/2
a = -3
a + b = 4
-3 + b = 4
b = 4 + 3
b = 7
a = -3 e b = 7
y = ax + b
y = -3x + 7
F(x) = -3x + 7
F (7) = -3.(7) + 7
F (7) = -21 + 7
F (7) = -14
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás